Removal of manganese from synthetic wastewater by adsorption - Jou, Wendy Kong Yin (2013)
Heavy metals are considered as pollutants in variety of industrial effluents and it is considered as a serious environmental problem. Industries release various concentration and amounts of heavy metals into water. However, when using groundwater as drinking water, manganese removal has become a problem especially in big cities. The objectives of this research was to synthesize and characterize of MOCZ for the removal of Mn2+ from synthetic wastewater by conducting the effect of contact time, adsorbent dosage, pH and initial Mn2+ concentration on adsorption capacity. The equilibrium data were fitted by using Langmuir and modified Langmuir isotherm model. Characterization of MOCZ were including specific surface area, pores volume, morphology properties and the mineralogical composition by using BET, FESEM and XRD respectively. Batch adsorption experiments were studied at different initial concentration from 50 mg/L to 200 mg/L at 150 rpm agitation speed for 120 min. The MOCZ showed low crystallinity degree, and the oxide coated on zeolite surface was presented mainly as vernadite (δMnO2) with specific surface area 39.9 m2g-1 and average pore size diameter of 1.1733 nm. Results showed that the amount of Mn2+ adsorbed increased with pH and adsorbent dosage and that the adsorption kinetics study of the Mn2+ followed a pseudo-second-order model. Furthermore, the two sites one molecule mechanism fitted well equilibrium data, showing a strong adsorption capacity for Mn2+ ions reaching a maximum capacity of 0.9267 meq Mn2+g-1. Results found showed that MOCZ showed a good potential as adsorbent for Mn2+ ions.